Development of FAZAR ALIRA Assisted PBL Materials to Enhance Students’ Scientific Literacy on the Human Circulatory System - Fatimatuz Zahro; Eko Hariyono; Binar Kurnia Prahani; Elok Sudibyo; Titin Sunarti; Fasih Bintang Ilhami; Syamsul Bahri HS (JPPS (Jurnal Penelitian Pendidikan Sains), 2026)
Objective: Innovative digital learning media are increasingly needed to help students understand complex biological concepts and develop scientific literacy. This study aimed to develop and evaluate the validity and practicality of FAZAR ALIRA, a learning media that integrates augmented reality (AR) visualization and virtual laboratory simulations within a PBL framework for teaching the human circulatory system. Method: The study employed a research and development approach consisting of analysis, design, development, and evaluation stages. The developed media includes AR visualizations of laminar and turbulent blood flow, contextual learning materials related to lifestyle and cardiovascular health, and interactive virtual laboratory simulations that allow students to investigate the relationship between blood vessel resistance, blood pressure, and heart workload. Results: The validity of the media was evaluated by science education experts and practitioners, while its practicality was examined through teacher and student responses during implementation. The results indicate that FAZAR ALIRA achieved high validity across content, construct, and language aspects and was considered practical and easy to use in classroom learning. Novelty: This study lies in integrating AR-based blood flow visualization, contextual health narratives, and virtual laboratory inquiry within a PBL environment to support students’ scientific literacy in learning the human circulatory system.